(untitled) (Fiep Bulletin - online, 2020)
Leprosy causes great damage to daily life and interpersonal relationships, causing suffering that goes beyond pain and discomfort strictly linked to physical impairment, with great social and psychological impact. The involvement of peripheral nerves is the main characteristic of leprosy, giving it a great potential to cause physical disabilities that may even develop into deformities. The objective of this study was to evaluate the degree of disability of leprosy patients based on the database of the Notification Disease Information System. It is a descriptive, observational and retrospective study. The population consisted of all leprosy patients notified by the local Epidemiological Surveillance. The sample consisted of 458 service notification forms from 2009 to 2012. The collection was performed by the Tabwin32 program, and the results were displayed in graphs and tables. Results: Most of the evaluated cases had zero disability degree in both evaluation moments, there was a decrease in the number of cases evaluated as grade I and II when compared at the time of diagnosis and cure. The most commonly observed clinical form was tuberculoid. Conclusion: The results of this work reinforce the relevance of developing health education actions so that there is early detection and proper management of identified cases. Keywords: Leprosy; Epidemiology; Public health.